Learning about sex and relationships among migrant and refugee young people in Sydney, Australia: 'I never got the talk about the birds and the bees'. Issue 6 (2nd November 2018) - Botfield, Jessica R.; Zwi, Anthony B.; Rutherford, Alison; Newman, Christy E.
Abstract: In a multicultural nation such as Australia, it is important for young people from migrant and refugee backgrounds to have access to quality relationships and sexuality education, as they are known to be less well engaged with mainstream services. A study was undertaken to explore the complexities and opportunities for engaging this group with sexual and reproductive health information and care in Sydney, Australia. Interviews were undertaken with 27 migrant and refugee young people (aged 16–24 years), and 34 expert informants. Relationships and sexuality education was a dominant theme throughout both data sets. Nearly all young people reported that they were unable to discuss sexuality or sexual health with their parents, and most identified secondary school as the place where they first learned about these issues. Other sources of information were identified as the Internet, friends, health professionals and pornography. Participants appeared to have limited awareness of the different services available to them. Schools, as well as other education settings such as universities, private colleges and intensive English centres, are well placed to deliver relationships and sexuality education, and for migrant and refugee young people these may be valuable settings in which to access information rarely discussed in family or community environments.